DETERMINANT OF DEVELOPMENT PERFORMANCE OF PT AURORA INDAH ELEKTRIK - Hutagalung, Zulkarnain; Robain, Wilchan (International Conference on Humanity Education and Society (ICHES), 2024)
This research aimed to find the effect of motivation, work discipline, and work environment, both partially and simultaneously, on the performance of PT Aurora Indah Elektrik employees. Respondent in this research was 48 contract employees. The sampling technique used was saturated sampling, and a questionnaire was used for collecting primary data. The research data were analyzed quantitatively using multiple linear regression methods with the help of the SPSS 24.0 application. The results of the quantitative analysis show that motivation, work discipline, and work environment both partially and simultaneously had a positive and significant effect on the performance of PT Aurora Indah Elektrik employees. Partial t-test results showed that motivation had tcount (3.904) > ttable (2.015) with a significance of 0.000 <0.05. Work discipline had tcount (2.853) > ttable (2.015) with a significance of 0.007 <0.05. The work environment had tcount (3.383) > ttable (2.015) with a significance of 0.002 <0.05. The simultaneous F test results showed that Fcount (212.105) > Ftable (2.816) with a significance of 0.000 <0.05. The most dominant variable affecting employee performance was the work motivation variable, with the largest tcount. The results of the determination test showed that 93.1% of employee performance could be explained and obtained from motivation, work discipline and work environment. In contrast, the rest was obtained from other factors. Employee performance strongly relates to motivation, work discipline, and work environment.